Correlation between knowledge of ecosystem concept based on local wisdom and environmental sensitivity with ecological behavior in SMAN 97 Jakarta - Sisi Hernanda Pratama; Diana Vivanti Sigit; Ratna Komala (EDUSAINS, 2025)
Several ecosystems have currently experienced damage due to several factors, both natural and due to human activities. Efforts to minimize this damage can be done by encouraging students to be aware of the natural resources around them, one of which is based on local wisdom. Awareness to love the environment must also be instilled in students, namely environmental sensitivity. Through ecosystem knowledge based on local wisdom and environmental sensitivity, students are expected to have ecological behavior. This research aims to (1) analyze the relationship between knowledge of ecosystem concepts based on local wisdom and ecological behavior, (2) analyze the relationship between environmental sensitivity and ecological behavior, (3) analyze the relationship between knowledge of ecosystem concepts based on local wisdom and environmental sensitivity with ecological behavior . This research uses quantitative descriptive methods. Respondents consisted of 168 students of class X Science at SMAN 97 Negeri Jakarta who were taken using a simple random sampling technique. The research results show that (1) there is a positive and strong correlation between knowledge of ecosystem concepts based on local wisdom and ecological behavior, (2) there is a positive and strong correlation between environmental sensitivity and ecological behavior, (3) there is a simultaneous positive and strong correlation between knowledge ecosystem concept based on local wisdom and environmental sensitivity with ecological behavior. The findings of this research are that consistency is needed in every activity carried out to improve students' ecological behavior.